Homicide and halo-halo - Manansala, Mia P. (Tita Rosie's Kitchen mysteries, 2022)
"Death at a beauty pageant turns Tita Rosie's Kitchen upside down in the latest entry of this witty and humorous cozy mystery series by Mia P. Manansala, author of Arsenic and Adobo. Things are heating up for Lila Macapagal. Not in her love life, which she insists on keeping nonexistent despite the attention of two very eligible bachelors. Or her professional life, since she can't bring herself to open her new café after the unpleasantness that occurred a few months ago at her aunt's Filipino restaurant, Tita Rosie's Kitchen. No, things are heating up quite literally, since summer, her least favorite season, has just started. To add to her feelings of sticky unease, Lila's little town of Shady Palms has resurrected the Miss Teen Shady Palms Beauty Pageant, which she won many years ago-a fact that serves as a wedge between Lila and her cousin slash rival, Bernadette. But when the head judge of the pageant is murdered and Bernadette becomes the main suspect, the two must put aside their differences and solve the case-because it looks like one of them might be next"--